Revascularization of Chronic Total Occlusion of the Infrarenal Aorta in a Patient with Triple Vessel Disease: Report of a Case Treated by Endovascular Approach - Mahek Shah; Soumya Patnaik; Rahul Sinha; Issac Opoku-Asare; Khalid Chaudhry; Sean Janzer (Case Reports in Cardiology)
Surgical management of advance aortoiliac occlusive disease is time-tested and a widely practiced strategy, particularly when there is significant coronary artery disease associated with aortoiliac occlusive disease. The technological advances in the field of percutaneous techniques have facilitated the use of nonsurgical endovascular alternatives for peripheral arterial disease in patients with significant comorbidities at high surgical risk, as illustrated in our case report. We report a case of chronic total occlusion of the aorta that was treated percutaneously with endovascular stenting. We also discuss the specific technique used in this procedure.